Winds of change a tale of: asthma and microbiome - Galeana-Cadena, David; Gómez-García, Itzel Alejandra; Lopez-Salinas, Karen Gabriel; Irineo-Moreno, Valeria; Jiménez-Juárez, Fabiola; Tapia-García, Alan Rodrigo; Boyzo-Cortes, Carlos Alberto; Matías-Martínez, Melvin Barish; Jiménez-Alvarez, Luis; Zúñiga, Joaquín; Camarena, Angel (Frontiers in Microbiology, 2023)
The role of the microbiome in asthma is highlighted, considering its influence on immune responses and its connection to alterations in asthmatic patients. In this context, we review the variables influencing asthma phenotypes from a microbiome perspective and provide insights into the microbiome's role in asthma pathogenesis. Previous cohort studies in patients with asthma have shown that the presence of genera such as Bifidobacterium, Lactobacillus, Faecalibacterium, and Bacteroides in the gut microbiome has been associated with protection against the disease. While, the presence of other genera such as Haemophilus, Streptococcus, Staphylococcus, and Moraxella in the respiratory microbiome has been implicated in asthma pathogenesis, indicating a potential link between microbial dysbiosis and the development of asthma.Furthermore, respiratory infections have been demonstrated to impact the composition of the upper respiratory tract microbiota, increasing susceptibility to bacterial diseases and potentially triggering asthma exacerbations. By understanding the interplay between the microbiome and asthma, valuable insights into disease mechanisms can be gained, potentially leading to the development of novel therapeutic approaches.